The role of the United Nations General Assembly in combating violence against women in peacetime - BOUTERAA, Chemama (Journal of Human Sciences, 2020)
The phenomenon of violence against women is considred as a worldwide phenomena that have attracted wide attention.Due to the aggravation of this phenomenon, what escalates and threatens the rights of women as human beings and the demolition of the principle of gender equality, this phenomenon was heared at the level of the United Nations, and took the  form of an offense and violation of human rights that the United Nations organization  is working to protect. This description of violence against women as a violation of human rights and women puts obligations on the United Nations level and the General Assembly to put the phenomenon among its top priorities in order to promote women's rights and protect them. Therefore, the General Assembly has made various efforts to fight violence against women since it is a phenomenon that hinder the achievement of security, Stability and development. thus efforts were made to reach international agreements and publishing declarations and laws relevant to the topic and conferences to issue a number of international resolutions.